Pendampingan Astrotourism untuk Meningkatkan Moderasi Beragama Masyarakat Desa Tanoh Alas Aceh Tenggara menggunakan Pendekatan Asset Based Community Development: Astrotourism Assistance to Increase Religious Moderation in the Community of Tanoh Alas Village, Southeast Aceh using an Asset Based Community Development Approach - Machzumy, Machzumy; Ihsan, Muhammad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Tanoh Alas Village, located in the Aceh province, is known for its multicultural character, with diverse ethnic groups, religions, and natural resources. Despite the long-standing coexistence of its residents, there remains a risk of religious conflicts, particularly those that are less visible. However, the village also offers an ideal environment for astrotourism. This has inspired the facilitators to focus on promoting religious moderation within the community. The key issues addressed in this initiative are: what strategies can be employed in astrotourism facilitation to enhance religious moderation in Tanoh Alas Village, and how do these strategies influence the community's attitudes toward religious moderation? The project utilized the Asset-Based Community Development (ABCD) approach, which encompasses the stages of Discovery, Dream, Design, Define, and Destiny. The outcome of this initiative has been a positive shift in religious moderation among the villagers, facilitated by the establishment of an astrotourism destination that fosters greater unity among different ethnic and religious groups.